Bentuk Film Dokumenter Ekspositoris Menggunakan Open Caption untuk Audiens dengan Keterbatasan Pendengaran - I Gede Nyoman Wisnu Satyadharma; Arthur S. Nalan; Retno Dwimarwati (PANTUN: Jurnal Ilmiah Seni Budaya, 2020)
The form of documentary film created in this this research is a documentary film art entitled "Berujar Dalam Sunyi". This is a documentary film with an expository style of exposure, using a comparative narrative style. This research is a creative process creating a documentary film of which applies the use of open caption to give access people with hearing impairments in Indonesia to documentary films. The issue of this research is the reality of the life of people with hearing impairments in Indonesia. This film uses koentjaraningrat’s seven elements of culture to explore the visual potential of the life of a deaf-deaf community. Access to films, especially documentary films for people with hearing impairments in Indonesia is still very limited. The form of access in question is open caption, which can help people with hearing impairments enjoy and understand the contents of a film which is an audio-visual art form. This research is a creative process of making documentary films applying the use of open captions to provide access to documentary films for deaf people in Indonesia. In its application, a combination of voiceover and open caption is used, so that this documentary film can be enjoyed by both hearing audiences and audiences with hearing impairments.The results of this study illustrate how to present the reality in the life of people with hearing impairments into a documentary film that can be enjoyed by audiences with hearing impairments.Keywords: Documentary Film, Expository Style, Comparative Narrative Style, Open Caption